Water losses in UiTM distribution network using GIS / Fauzi Baharudin, Muhamad Fuad Shukor and Hamidon Ahmad - Baharudin, Fauzi; Shukor, Muhamad Fuad; Ahmad, Hamidon (2011)
Non Revenue Water (NRW) has been a long standing issue in Malaysia. Under the Ninth Malaysia Plan (RMK-9), the government has placed a great attention towards the issue and has set a target to reduce the NRW from 38 percent to 30 percent by 2010. On a smaller scale, UiTM is also having a similar issue and it is important to start a comprehensive study to address the water loss problem. It is crucial to investigate the sources of the water loss and create a GIS framework for better representation of data and detail analysis. This research will significantly show understanding on the sources of water loss in UiTM and develop a reliable platform for analysis using GIS tools. The GIS platform can be used as a tool for decision making, especially for replacement of old pipes. Furthermore, this research contributes in optimizing the water distribution system and significantly reduce the annual utility (water) bill for UiTM.